Numerical Solutions of the Stagnation-Point Flow and Heat Transfer Towards An Exponentially Stretching/ Shrinking Sheet with Constant Heat Flux - Alavi, Sayed Qasim; Norhayati, Rosli; Mohd Zuki, Salleh (2015)
The steady stagnation point flow and heat transfer towards an exponentially stretching/shrinking sheet with constant heat flux is investigated in this paper. The transformed governing nonlinear boundary layer equations are solved numerically by using Runge-Kutta-Fehlberg method. Numerical solutions are obtained for the local wall temperature, local skin-friction coefficient as well as velocity and temperature profiles. The features of the flow and heat transfer characteristics for different values of the stretching/shrinking parameter and the Prandtl number are analyzed and discussed.